2015
DOI: 10.3899/jrheum.140630
|View full text |Cite
|
Sign up to set email alerts
|

Surface APRIL Is Elevated on Myeloid Cells and Is Associated with Disease Activity in Patients with Rheumatoid Arthritis

Abstract: Objective To assess surface APRIL (a proliferation-inducing ligand; CD256) expression by circulating myeloid cells in rheumatoid arthritis (RA) and to determine its relationship to disease activity. Methods Peripheral blood mononuclear cells (PBMC) and plasma were obtained from patients with RA and healthy donors. PBMC were stained for flow cytometry to detect surface APRIL and blood cell markers to identify circulating myeloid cell subsets. Based on CD14 and CD16 phenotypes, monocyte subsets described as cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 51 publications
1
27
0
Order By: Relevance
“…Based on their expression of the surface markers CD14 and CD16 three major subsets defined as CD14++CD16− for classical monocytes, CD14++CD16+ for intermediate monocytes and CD14+CD16+ for non-classical monocytes can be distinguished in men 3 . Several clinical studies point towards an association of CD16+ subsets with pathologies characterized by a chronic inflammatory state such as coronary artery disease, obesity, arthritis, inflammatory diseases of the intestinal tract or systemic lupus erythematous 8 29 30 31 32 .…”
Section: Discussionmentioning
confidence: 99%
“…Based on their expression of the surface markers CD14 and CD16 three major subsets defined as CD14++CD16− for classical monocytes, CD14++CD16+ for intermediate monocytes and CD14+CD16+ for non-classical monocytes can be distinguished in men 3 . Several clinical studies point towards an association of CD16+ subsets with pathologies characterized by a chronic inflammatory state such as coronary artery disease, obesity, arthritis, inflammatory diseases of the intestinal tract or systemic lupus erythematous 8 29 30 31 32 .…”
Section: Discussionmentioning
confidence: 99%
“…In several clinical studies an association of CD16 þ subsets with such pathologies has been described. [10][11][12] Our results presented here suggest that mostly the CD16 À Mon1 subset responds to inflammatory activation with an upregulation of PAR1 and PAR3. It would therefore be of interest to determine in future studies if also in chronic inflammatory In vivo and in vitro regulation of plasminogen activator inhibitor-1 (PAI-1) and tissue factor (TF) through PAR1.…”
Section: Discussionmentioning
confidence: 81%
“…8,9 In various clinical studies an association of CD16 þ subsets with pathologies characterized by a chronic inflammatory state such as coronary artery disease, obesity, arthritis, inflammatory diseases of the intestinal tract, or systemic lupus erythematosus has been described. [10][11][12][13][14] Recently, we showed that Mon2 were associated with 30-day mortality in critically ill patients. 15 Furthermore, we established in a human endotoxemia model that especially CD16 þ cells respond to lipopolysaccharide (LPS)-induced activation with an increased production of the inflammatory cytokines interleukin-6 (IL-6) and IL-8.…”
Section: Introductionmentioning
confidence: 99%
“…Accumulation of APRIL-secreting cells has also been observed in synovial tissues of RA patients. Moreover, in comparison to healthy individuals of which APRIL expression are only detected in nonclassical monocytes, myeloid cells and all monocytes in RA patients exhibited upregulation of surface APRIL expression with an association to disease severity [ 137 ]. Stimulation of synoviocytes from the patients also resulted to higher production of pro-inflammatory cytokines and upregulation of receptor activator of nuclear factor kappa-B ligand (RANKL) expression.…”
Section: Breg-inducing Cytokinesmentioning
confidence: 99%